Financial burden and financial toxicity in patients with colorectal, gastro-oesophageal, and pancreatobiliary cancers: A UK study. (September 2020) - Flaum, Nicola; Papaxoinis, George; Hockenhull, Kimberley; Barrusio, Jorge; Backen, Alison; Cunningham, David; Mansoor, Wasat
Highlights: We describe the first study of financial burden and toxicity in UK cancer patients. 38 % of patients studied experienced financial burden and 20 % financial toxicity. Younger age, more deprived background and tumour type predicted financial burden. No baseline characteristic predicted financial toxicity. Tumour type, palliative treatment and deprived background predicted poorer survival. Abstract: The financial impact of cancer on patients in the UK is poorly understood. We assessed financial burden (FB), defined as financial impact on patient at diagnosis and financial toxicity (FT), defined as financial impact throughout treatment, in patients with upper gastrointestinal UGI), pancreatobiliary (PB) and lower GI (LGI) cancers. Patients enrolled in 5 clinical trials (REAL-3, RAINFALL, ESPAC-4, QoL BIL and CAPITAL) at the Christie, Manchester, were identified. FB at baseline and FT throughout treatment were defined according to answers to the EORTC QLQ-C30 questionnaire (EQ) Q28 to which patients score financial difficulty relating to disease/treatment from 1 (not at all) to 4 (very much). 141 patients were identified, 68.1 % were male; median age was 62 years (range 39–94). 15 (10.6 %) patients had LGI, 85 (60.3 %) PB and 41 (29.1 %) UGI cancer. 62 % had no FB, 25 % 'a little', 9% 'quite a bit' and 5% 'very much'. 63.5 % experienced no FT, 19.8 % worse FT and 16.7 % improved FT. Multiple regression analysis showed that younger age, lower index of multiple deprivation (IMD) and tumour type were independent predictors of FB. Significant covariates included escalating IMD (OR 0.78, 95 %CI 0.68−0.92, p = 0.002), age above vs. below median (OR 0.10, 95 %CI 0.04−0.24, p < 0.001) and PB cancers (OR 3.66, 95 %CI 1.34–10.03, p = 0.012). Escalating IMD was associated with better OS (HR 0.90, 95 %CI 0.84−0.98, p = 0.010). We report the first study of FB and FT in cancer patients in the UK, identifying independent baseline parameters predicting FB and the prognostic role of IMD.